Redescription of the adults of Culicoides bancrofti Lee and Reye and C. hornsbyensis Lee and Reye (Diptera: Ceratopogonidae) - Bellis, Glenn; Dyce, Alan (Zootaxa, 2012)
The Bancrofti species group of the biting midge genus Culicoides Latreille which embraces two species from Australia and Papua New Guinea is revised. A diagnosis for the group along with a first description of adult male C. bancrofti Lee & Reye and redescriptions of female adult C. bancrofti  and male and female adult C. hornsbyensis Lee & Reye are presented together with keys for their specific determination.